Gender differences in Generalized Anxiety Disorder: Results from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) - Vesga-López, Oriana (J Clin Psychiatry, 2008)
OBJECTIVE: To assess gender differences in the epidemiology, comorbidity and treatment-seeking patterns of DSM-IV Generalized Anxiety Disorder (GAD) in the United States. METHOD: Data were derived from the 2001–2002 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), a large cross-sectional survey of a representative sample (N=43,093) of the U.S. population. RESULTS: The lifetime and twelve-month male:female prevalence ratios of DSM-IV GAD were 1:1.9 and 1:2.2, respectively. Men with GAD had significantly higher rates of comorbid alcohol and drug use disorders, nicotine dependence, and antisocial personality disorder. Women with GAD had significantly higher rates of comorbid mood disorders (except bipolar disorder) and anxiety disorders (except social anxiety disorder). Men with GAD reported greater use of alcohol and non-prescription medications to help relieve GAD symptoms. GAD in women was associated with higher family history of depression. Disability associated with GAD was greater in women than in men. Rates of treatment-seeking for DSM-IV GAD were low for both genders, but particularly low among men. CONCLUSION: There are significant gender differences in the prevalence, comorbidity pattern, sociodemographic and clinical correlates, course, and treatment-seeking rates of persons with DSM-IV GAD. Increased recognition and treatment of GAD, particularly among men, could lead to a substantial reductions in the societal and personal burden and improve the quality of life of those afflicted with this disorder.